(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The deformation method allows to describe the stress-strain state of foundation structures by means of dependency that binds settling of foundations to the parameters of stiffness in the system «base – piles foundation» at different stiffness coefficients of the basis, along length or depth of foundation. The proposed methodology allows improving the calculations of the stress-strain state of laterally loaded piles, which can significantly improve the performance of buildings and structures. Deformations of a foundation structure are described by approximate dependency that includes the sinking of ends of foundation and the stiffness parameter of the system "basis-foundation". The calculation embraces various (linear and nonlinear) distributions patterns of the of the stiffness coefficient of the basis along the length of the structure as well as distribution properties of the ground basis.